Pengaruh Kesalahan Ejaan Remaja terhadap Citra Diri dalam Media Sosial - Wardhani, Bintang Kusuma; Irawan, Novan Andi Nanang; Adithya, Muhammad Rifky (FKIP Unirow Tuban, 2024)
This article discusses the impact of spelling errors on adolescent self-image on social media platforms. The main issues involve the influence of speech errors upon the level of self-confidence, feelings of shame or inferiority, as well as the perception of others in the social media environment. Using qualitative methods, namely interviews and observations, the study aims to thoroughly investigate the impact of spelling errors on adolescent self-image. Others see it, which affects social interactions and relationships on social media. One of the real results of this article is increased attention to the correct use of language in social media and a better understanding of how it affects adolescent self-image. It is hoped that this article will be the basis for the development of educational and intervention programmes that raise adolescent awareness of the importance of using the right language in social media to build a positive self-image.